THE EFFECT OF USING FLASHCARDS MEDIA TO INCREASE VOCABULARY SIZE FOR THE SECOND-GRADE STUDENTS AT MTs MADANI ALAUDDIN - Siti Hardiyanti Pratiwi,; Andi Asmawati,; Indah Miftah Awaliah, (English Language, Linguistics, and Culture International Journal, 2022)
This research aims to find out the effect of Flashcards media to increase vocabulary size for the second grade students at Mts Madani Alauddin. This research was conducted at Mts Madani Alauddin Regency in academic year 2021/2022. The researcher used the instrument to collect data Vocabulary Size Test and Vocabulary Level Test (VLT). This research used quantitative data applied a pre-test and post-test group design, in this research the population were 145 students of the second grade at Mts Madani Alauddin. The sample were 20 students of Class VIII A as an experimental class using the pre-experimental design method, type one group pretest-posttest (single group initial test). The research findings showed that the second grade of students at Mts Madani Alauddin obtained scores on the pre-test with a mean score of 50.5, which was classified as very poor. After giving treatment, they obtained a score with a mean score of 65.5, which was classified as fair. It means that there was a significant increase in students’ vocabulary size using Flashcard media it was supported by the results of the one-sample T-Test where sig. (2-tailed) 0.001 < 0.05 has an effect in increasing students’ vocabulary. Therefore Ho is rejected and H1 is accepted, apart from that the results of the vocabulary level test showed that the average student got a fair score. The result of the data analysis indicated that there was the improvement in the students’ vocabulary size after being taught using Flashcard media.